Spatial variation of harvested rainwater quality in South Vavuniya, Sri Lanka - Lajeekka, Jeevaraththinam; Saravanan, S.; Vijitha, V.; Vijayabalan, J. (Universitas Nahdlatul Ulama Surabaya, 2023)
Rainwater is one of the vital natural resources which plays crucial role in water cycle. Rainwater harvesting is a water conservation technique in which rainwater is captured and stored for various purposes. Despite being an excellent practice, rainwater harvesting does come with some challenges. As poor quality of harvested rainwater due to several natural and anthropogenic activities is one of such limitations, the current study was aimed to assess the water quality of harvested rainwater in Vavuniya south, Sri Lanka. For this study 189 samples were collected from Vavuniya south and the water quality parameters such as color, turbidity, coliform, E. coli, electrical conductivity (EC) and pH were analyzed. Further the recorded water quality data were mapped using ArcMap 10.8 software. Among the 189 water samples, 88% showed color below 1 Hazen while 12% showed color level above 1 Hazen. Notably, 7% of the samples exceeded a color value of 15 Hazen. Regarding the turbidity, 99% of the samples exhibited below 5 NTU. Out of the 189 water samples, 23% showed 0 Nos/100 mL coliform whereas 77% had coliform counts more than 3 Nos/100 mL. At the same time 57% of samples showed E. coli count lower than 10 Nos/100 mL among which 52% samples showed 0 Nos/100 mL numbers of E. coli. Among the 189 water samples, 43% samples showed E. coli numbers above 10 Nos/100 mL. Further, 95% samples showed EC below 200 µS/cm and 5% of the samples showed EC above 200 µS/cm. In addition, majority of the samples (80%) fell within the pH range of 6.5 to 8.5 while remaining 15% showed pH below 6.5 and 5% showed pH above 8.5. Based on the study, soil dust particles, fecal contamination, metal rooftops and emissions from development activities were found as possible causes for recorded poor harvested rainwater quality in some areas. Moreover, the samples analyzed from areas namely South Paravakkulam, Periya Ulukkulama, Avusathapittiya, Rangethgama, Kalukunnamaduva, Alagalla and Eratperiyakulama exceeded the standard range of water quality for at least two parameters. Therefore, regular maintenance and monitoring are required in these areas to ensure safe consumption of rainwater for various uses.